ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DI KUA KECAMATAN MANTUP KABUPATEN LAMONGAN - Aji Wahyu Susanto; Yunita Ardilla; Airlangga Bramayudha (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This study uses a qualitative approach to analyze the implementation of the Marriage Management Information System (SIMKAH) at the KUA Mantup District, Lamongan Regency, and its contribution to improving the quality of marriage administration services. Data were collected through in-depth interviews with the head and employees of the KUA, direct observation for 40 days, and documentation of various supporting data. The analysis was carried out using the DeLone and McLean Information System Success Model which includes six dimensions: system quality, information quality, usage, user satisfaction, service quality, and net benefits. Triangulation techniques were used to ensure data validity by combining various sources and methods. The results of the study indicate that SIMKAH has a positive impact on work efficiency, data transparency, and service accessibility, although there are still technical constraints and limited public understanding. Overall, SIMKAH plays a role in supporting the modernization of digital-based public services and is in line with Islamic values ​​in maintaining the validity and order of marriage.